Legal Certainty Regarding The Cancellation Of Arbitration Awards In District Courts - Juniarty, Santy; Setiawan, Puguh Aji Hari; Iryani, Dewi (Ilmu Hukum Prima (IHP), 2025)
Arbitration in Indonesia, based on Law Number 30 of 1999, is designed as a dispute resolution mechanism that provides legal certainty through its final and binding decisions. This principle, known as das sollen, is expected to support a conducive investment climate. However, in practice (das sein), Article 70 of the same law authorizes the District Court to annul arbitration awards. The implementation of this authority, particularly on grounds of "trickery," often leads to inconsistencies in court decisions. This study uses a normative juridical research method with a statute approach and a conceptual approach. Data collection was conducted through library research on primary, secondary, and tertiary legal materials. The collected data were then analyzed qualitatively using systematic, theological, and grammatical interpretations. To analyze legal issues in depth, this study uses the Theory of Legal Certainty and the Theory of Agreements as analytical tools for three relevant case studies of Supreme Court decisions: Decision Number 941 B/Pdt.Sus-Arbt/2024, Decision Number 244 B/Pdt.Sus-Arbt/2022, and Decision Number 477 B/Pdt.Sus-Arbt/2022. The research findings indicate that the legal basis and considerations of judges in annulling arbitral awards are in accordance with legal provisions only if they are based on violations of fundamental principles in the legal process, such as the existence of legally proven fraud that affects the legal standing of the parties or the integrity of the process. However, court intervention becomes unlawful when re-examining the substance of the dispute, because it violates the autonomy of the parties' will. It is concluded that legal certainty regarding the annulment of arbitral awards is in a vulnerable condition due to inconsistent interpretations of judges. This inconsistency directly weakens the predictability of law and the principle of finality of arbitration, which has implications for declining investor confidence in the domestic dispute resolution system.